1101 Urine complement activation products in lupus nephritis. (14th December 2022) - Li, Nicholas; Birmingham, Daniel J; Biederman, Laura; Nadasdy, Tibor; Rovin, Brad H
Abstract : Background: Complement activation plays a critical role in the development of kidney injury during lupus nephritis (LN). Clinical trials targeting the complement pathway are now underway in LN. It is therefore important to understand the relationship between intra-renal complement activation and kidney histology in LN, and whether complement activation products (CAPs) can serve as biomarkers to guide complement-directed therapies. In this investigation, urine CAPs levels were measured, and associations with kidney injury were determined. Methods: A cohort of 149 patients had urine and blood collected at the time of kidney biopsy for suspected LN. The CAPs C5a, C5b-9, and factor Ba were measured in the urine by ELISA. Biopsies were examined by routine histology, and the NIH activity and chronicity indexes (AI, CI) were calculated by two nephropathologists. CAPs levels were correlated with clinical and histologic data using the spearman correlation r. Results: The results are summarized in the table 1. The highest levels of CAPs were found in patients with proliferative or proliferative plus membranous LN, with lower levels in pure class II and V. All three urine CAPs correlated with AI, but the strongest correlation was between C5b-9 and AI. Only Ba and C5a correlated with CI, but this correlation was, at best, modest. All CAPs correlated with proteinuria, while only Ba and C5a correlated with serum creatinine. Conclusion: Urine C5b-9 was the best measure of histologic activity in LN. Given the size of the C5b-9 complex, it is unlikely to be filtered, even by glomeruli with a damaged glomerular permeability barrier. Urine C5b-9 therefore only reflects intra-renal complement activity. C5a and Ba associated modestly with active lesions, as well as kidney damage, likely accounting for their association with serum creatinine. We suggest levels of urine C5b-9 could be used to follow the success of anti-complement therapies in mitigating intra- renal complement activation in LN.